Physics of clusters - Lakhno, V.D (World Scientific, 1998)
"Based on talks given at the Cluster Workshops, which were held in Pushchino in 1995 and 1996"--preface.; Includes bibliographical references.; The monograph is devoted to the relatively new and fast developing field of cluster physics. It is based on talks given at the Cluster Workshops, which were held in Pushchino in 1995 and 1996. The reports focus not only on the fundamental physical properties of clusters such as their geometric and electronic structure, as well as optical, thermal and magnetic properties, but also on a broad spectrum of their potential applications. These include nucleation and growth of small particles, fabrication of new materials with predefined properties (cluster-assembled and nanostructures). Some aspects of simulations and calculations of small particles and clusters are also discussed.